Demonstration of an intracellular copper-binding protein by orcein staining in long-standing cholestatic liver diseases. Issue 10 (October 1976) - Salaspuro, M; Sipponen, P
Abstract : Liver biopsies from eight patients with primary biliary cirrhosis, two with chronic active hepatitis of a cholestatic form, three with long-standing alcoholic liver cirrhosis, and one with extrahepatic biliary obstruction were studied. In each case dark brown cytoplasmic material was seen after staining of the tissue sections with Shikata's orcein method. In exactly the same cellular and subcellular locations as the orcein-positive material, and with morphologically equal granules, two different ordinary staining methods for copper (rubeanic acid and Mallory-Parker's haematoxylin) gave positive reactions. The earlier histochemical findings have revealed the protein nature and high sulphydryl content of the orcein-positive material. Its close association with copper in liver sections suggests its copper-binding nature and indicates that a common copper-protein complex accumulates in the cytoplasm of liver cells during longstanding cholestasis in biliary diseases of various pathogenetic origin.